Mosquitoes, Malaria, and Cold Butter: Discourses of Hygiene and Health in the Panama Canal Zone in the Early Twentieth Century - Sarah J. Moore (Panorama, 2017)

(untitled)
Discourses of health, hygiene, and progress—visual and textual—provide the primary metric with which to recalibrate thinking about the Panama Canal enterprise and zone as an ecology located at the nexus of intersecting discourses.